1995
DOI: 10.1097/00000542-199503000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Heat Flow and Distribution during Induction of General Anesthesia 

Abstract: The arms and legs are both important components of the peripheral thermal compartment, but distal segments contribute most. Core hypothermia during the first hour after induction resulted largely from redistribution of body heat, and redistribution remained the major cause even after 3 h of anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
228
1
9

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 492 publications
(245 citation statements)
references
References 39 publications
3
228
1
9
Order By: Relevance
“…Vasodilatory response to histamine released from brain mast cells induced by general anesthetics, opiods, and muscle relaxants through the circumventricular organ near the third ventricle, which lacks the blood-brain barrier [27], may play a role in vasodilation in general anesthesia [9]. In a study of core temperature changes in healthy volunteers undergoing general anesthesia, Matsukawa et al [16] found that core temperature decreased 1.6 ± 0.3°C in the 1st h of anesthesia. During the subsequent 2 h, core temperature decreased an additional 1.1 ± 0.3°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasodilatory response to histamine released from brain mast cells induced by general anesthetics, opiods, and muscle relaxants through the circumventricular organ near the third ventricle, which lacks the blood-brain barrier [27], may play a role in vasodilation in general anesthesia [9]. In a study of core temperature changes in healthy volunteers undergoing general anesthesia, Matsukawa et al [16] found that core temperature decreased 1.6 ± 0.3°C in the 1st h of anesthesia. During the subsequent 2 h, core temperature decreased an additional 1.1 ± 0.3°C.…”
Section: Discussionmentioning
confidence: 99%
“…These losses are trivial compared to the effect of general anesthesia. Data regarding heat loss due to anesthesia were obtained from Matsukawa et al [16].…”
mentioning
confidence: 99%
“…After rapid initial core hypothermia during anesthesia induction, which results from inhibition of tonic thermoregulatory vasoconstriction, a core temperature plateau occurs because of emergence of thermoregulatory vasoconstriction, in which cutaneous heat loss and metabolic heat production are in balance [6][7][8]. Therefore, failure of effective prevention of hypothermia by amino acid infusions at the commencement of anesthesia is probably because heat loss by redistribution of body heat is much greater than thermogenesis by amino acids during induction of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Core hypothermia during general anesthesia develops with three characteristic phases [6][7][8]. Initial core hypothermia results from core-to-peripheral redistribution of body heat when anesthesia inhibits tonic thermoregulatory vasoconstriction.…”
Section: Introductionmentioning
confidence: 99%
“…Dass sich durch Medikamente eine Hypothermie auslösen lässt, ist für den Anästhe-sisten keine neue Erkenntnis: Während einer längeren Narkose nimmt die Körper-kerntemperatur des Patienten ohne aktive Wärmemaßnahmen regelhaft um mehrere Grad ab [32]. Ursächlich sind hierfür zum einen eine periphere Vasodilatation und damit ein Abfluss von Wärme aus dem Körperkern, zum anderen eine Reduktion der metabolischen Wärmepro-…”
Section: Beobachtungen Aus Der Klinikunclassified